A vida ficcional das coisas em A hora da estrela de Clarice Lispector - Almeida, Diana Carla Gomes de (2019)
This study aims to analyze the objects present in A hora da estrela of the Clarice Lispector and how they significantly influence the "life" of the characters, especially the protagonist Macabéa, because of marking presence in the fictional setting. The s